MODEL' UPRAVLENIYA ATTESTATSII INZHENERNO-PEDAGOGICHESKIKH KADROV - T. S. Yurtaeva (Вестник Мининского университета, 2017)
This paper deals with the essence of engineering and certification of teachers in vocational school purposes on the basis of modern vocational education aimed at the development of personal qualities and professional and educational activities of teachers, trainers, providing socialization and professionalization of the individual, raising the level of professional competence. The model of control engineering and certification of teachers, considered as a factor stimulating teaching staff to effective professional activity, the mechanism of self-diagnosis and professional and educational activities.